STAFFING PROBLEMS AND SOLUTIONS IN THE COURT SYSTEM OF UZBEKISTAN (Western European Journal of Modern Experiments and Scientific Methods, 2024)
The article historically analyzes the processes related to personnel in the judicial system of Uzbekistan and their outcomes.